Rare earth compound functional filler for antibacterial and deodorant socks and preparation method of rare earth compound functional filler

The rare earth composite functional filler prepared by precipitation and adsorption combined with the synergistic effect of rare earth ions, zinc ions and silver ions, solves the problem that the antibacterial antibacterial agent of existing antibacterial and odorant socks is not lasting, and achieves the long-term antibacterial and deodorant effects of rare earth composite functional filler in antibacterial and anti-odorant socks.

CN119710955APending Publication Date: 2025-03-28AICHIER (HAINAN) HOLDINGS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411992063.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The antibacterial agents of existing antibacterial anti-odor socks are not lasting, and the antibacterial ability of the carrier is weak, making it difficult to synergize with highly effective antibacterial metal ions.

Method used

Rare earth composites are prepared as antibacterial agents by precipitation and adsorption methods, and rare earth composites are used as functional fillers for antibacterial and anti-odor socks. The antibacterial and deodorant properties are enhanced through the synergy of rare earth ions with zinc ions and silver ions.

Benefits of technology

The long-term antibacterial and deodorizing effect of rare earth composite functional fillers in antibacterial and anti-odor stockings is achieved, and its performance is better than the traditional Ag and Zn2+ loading effect on the carrier, and it has beneficial properties such as promoting angiogenesis, osteogenesis and wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710955A_ABST
    Figure CN119710955A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth compound functional filler for antibacterial and deodorant socks and a preparation method thereof, and relates to the field of textile material science, and the preparation method comprises the following steps: S1, preparing rare earth and zinc carbonate; s2, preparing a rare earth compound; according to the rare earth compound functional filler for the antibacterial and deodorant socks and the preparation method of the rare earth compound functional filler, the scaly carrier in the prepared rare earth compound functional filler has antibacterial and deodorant functions, and is synergistically antibacterial and deodorant with Ag and Zn < 2 + >, the performance of the rare earth compound functional filler is superior to that of the carrier loaded with Ag and Zn < 2 + > on zeolite, sodium zirconium phosphate, SiO2 and the like, and the rare earth compound functional filler not only has the antibacterial and deodorant functions, but also has the antibacterial and deodorant functions. The rare earth compound functional filler is added into the sock base material, has the beneficial characteristics of promoting angiogenesis, osteogenesis, wound healing and the like and has important significance in keeping feet clean and healthy, the rare earth compound functional filler is added into the sock base material, the woven socks have heat resistance, flame retardance, aging resistance, wear resistance and heat insulation performance, and the prepared antibacterial and deodorant socks have broad-spectrum and lasting antibacterial and deodorant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to textile material science and technology, and in particular to a rare earth composite functional filler for antibacterial and deodorizing socks and a preparation method thereof. Background Art

[0002] As people pursue a healthier and more comfortable life, the demand for antibacterial and deodorizing socks in the civilian market is growing. For example, in travel, leisure, work and other occasions, antibacterial and deodorizing socks are needed to keep the feet clean and dry.

[0003] At present, antibacterial and deodorizing technologies mainly use inorganic compounds, bamboo charcoal and organic antibacterial technologies. Inorganic compounds have the function of killing and inhibiting microorganisms. Commonly used antibacterial metals mainly include silver, copper, zinc, magnesium, molybdenum, etc. The invention patent with the authorization announcement number CN105901782B discloses a method for preparing pearl antibacterial and deodorizing socks. The invention uses raw vermiculite powder as a carrier of silver to obtain an expanded vermiculite-nanosilver composite material; silver is the main antibacterial material in this composite material, and expanded vermiculite has a certain adsorption capacity for odor in the environment, but the adsorption and deodorization rate is slow and the adsorption effect is limited. Vermiculite does not have the function of decomposing odor compounds, and does not have the synergistic antibacterial function of combining with silver ions.

[0004] The invention patent with authorization announcement number CN106473240B discloses a preparation process of nano silver wire antibacterial and deodorant socks. The invention is to disperse the silver wire in a solution, bond it to the inner surface of the socks through an impregnation treatment process, and then dry it to obtain the antibacterial and deodorant socks; the silver wire is loaded on the surface of the socks by the impregnation method, and the socks have a good antibacterial and deodorant effect in the early stage. As the friction and water washing times increase, the silver wire falls off the surface of the socks, and the antibacterial performance will be greatly attenuated, and the long-term antibacterial and deodorant effect cannot be maintained.

[0005] Zinc ions also have antibacterial activity, but the antibacterial activity of zinc ions is only 1 / 1000 of that of silver ions. However, the antibacterial activity of zinc oxide can be significantly improved by doping with rare earth elements. The invention patent with authorization announcement number CN105648745B discloses a polymer-based cerium-doped nano zinc oxide composite antibacterial agent for fabrics and a preparation method thereof. In this method, zinc and cerium react with sodium hydroxide to form a precipitate, and the precipitate is freeze-dried to obtain cerium-doped nano zinc oxide, wherein the molar ratio of cerium to zinc is 0.5%-3%; freeze-drying of this method should obtain a mixture of zinc hydroxide and cerium hydroxide, and only after high-temperature decomposition can cerium-doped nano zinc oxide be obtained. The high-temperature decomposition process is also a process of agglomeration of cerium-doped zinc oxide, and the patent content does not specify the high-temperature decomposition process.

[0006] Inorganic antibacterial agents are mostly natural zeolite, montmorillonite, kaolin, etc. and chemically synthesized sodium zirconium phosphate, SiO 2 、TiO 2Ion exchange materials are used as carriers, and silver, copper, zinc, etc. are loaded as antibacterial active ingredients. The invention patent with the authorization announcement number CN1313005C discloses a rare earth activated silver-loaded inorganic antibacterial agent and its preparation method, using sodium zirconium hydroxyphosphate as a silver, zinc, and copper antibacterial ion carrier, and using rare earth activation to improve its antibacterial properties. The antibacterial agent has strong antibacterial ability. The invention patent with the authorization announcement number CN101176468B discloses an inorganic composite antibacterial agent containing zinc-rare earth, its preparation method and application. The antibacterial agent loads zinc ion and rare earth ion dual active centers through ion exchange method, the zinc ion content is 6.0-8.0wt%, and the rare earth ion content is 2.0-4.0wt%. The zinc ion and rare earth ion in the antibacterial agent serve as synergistic antibacterial active centers with a wide antibacterial spectrum and high antibacterial efficiency. However, the exchange material carriers in these patents, whether natural or chemically synthesized, have weak or no antibacterial ability. Research and development of carriers with antibacterial functions that can cooperate with high-efficiency antibacterial metal ions to improve their antibacterial ability and reduce the amount of antibacterial metal ions added.

[0007] In recent years, rare earth compound antibacterial materials have received widespread attention worldwide. Due to its special 4f electron layer structure, cerium oxide, in particular, can be doped with other rare earth oxides to change its physical and chemical properties. 3+ and Ce 4+ The oxidation states between them can be reversibly converted to serve as an effective bactericidal agent, but cerium oxide alone is not effective as an antibacterial agent. The antibacterial activity is significantly enhanced by doping with antibacterial metal ions. Summary of the invention

[0008] In view of this, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a rare earth composite functional filler for antibacterial and deodorant socks and a preparation method thereof, and to prepare the rare earth composite as an antibacterial agent by precipitation and adsorption method, and the rare earth composite is used as a functional filler for antibacterial and deodorant socks.

[0009] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks, comprising the following steps:

[0010] S1. Preparation of rare earth and zinc carbonates: Add bottom water to the reactor, heat the bottom water temperature to 35°C under stirring, and then slowly add La with a concentration of 0.48 mol / L x Ce (1-x) Cl 3 solution and 2.28 mol / L ammonium bicarbonate solution, maintaining the pH of the reaction system at 6.5, La x Ce (1-x) Cl 3 After the solution was added, (La x Ce (1-x) )2 (CO 3 ) 3 Precipitation, then continue to slowly add a 1.23 mol / L zinc chloride solution and a 2.28 mol / L ammonium bicarbonate solution at the same time, maintain the pH of the reaction system at 7, after the zinc chloride solution is added, the obtained precipitate is washed several times until the washing filtrate is detected by silver nitrate without precipitation, and filtered to obtain flaky rare earth and zinc carbonate;

[0011] S2. Preparation of rare earth composites: Add a certain amount of water and dispersant into a reactor, add rare earth and zinc carbonate under stirring to form a uniformly dispersed suspension, add the suspension into a silver nitrate solution containing a dispersant, stir and react for 4 hours, centrifuge and dehydrate, and calcine the obtained solid powder at a temperature of 500°C for 2 hours. Grind the calcined solid powder to a powder particle size of less than 1 μm to obtain a rare earth composite functional filler.

[0012] Furthermore, in step S1, La x Ce (1-x) Cl 3 For La 0.1 Ce 0.9 Cl 3 ,La 0.36 Ce 0.64 Cl 3 and La 0.5 Ce 0.5 Cl 3 One of;

[0013] La x Ce (1-x) Cl 3 The solution is composed of La x Ce (1-x) Cl 3 , water and acetic acid, La x Ce (1-x) Cl 3 The mass ratio with acetic acid is 1:0.014.

[0014] Furthermore, in step S2, the mass concentration of rare earth and zinc carbonate in the suspension is 10%, the amount of dispersant added is 1% of the mass of water, and the dispersant is polyvinyl pyrrolidone.

[0015] Furthermore, the silver nitrate solution containing a dispersant in step S2 is composed of silver nitrate, a dispersant and water, the mass concentration of silver nitrate in the solution is 10%, the amount of the dispersant added is 0.1% of the mass of the silver nitrate, and the dispersant is polyvinyl pyrrolidone.

[0016] Furthermore, in step S2, the molar ratio of rare earth ions to zinc ions in the rare earth composite functional filler is 1:0.10-0.21, and the molar ratio of rare earth ions to silver is 1:0.01-0.03.

[0017] Furthermore, in step S2, the rare earth composite functional filler is Ag, ZnO, La 2 O 2 CO 3 and CeO 2 The composition of the solid solution.

[0018] As a general technical concept, the present invention also provides the rare earth composite functional filler prepared by the above method as an antibacterial and deodorant agent, and the use of the rare earth composite functional filler in antibacterial and deodorant socks.

[0019] Compared with the prior art, the present invention provides a rare earth composite functional filler for antibacterial and deodorizing socks and a preparation method thereof. The flaky carrier in the prepared rare earth composite functional filler has antibacterial and deodorizing functions, and is combined with Ag and Zn 2+ Synergistic antibacterial and deodorizing performance, better than Ag and Zn 2+ Supported on zeolite, sodium zirconium phosphate, SiO 2 etc. carriers;

[0020] The rare earth composite functional filler prepared by the method of the present invention not only has antibacterial and deodorizing functions, but also has beneficial properties such as promoting angiogenesis, osteogenesis and wound healing, which is of great significance for keeping feet clean and healthy.

[0021] The rare earth composite functional filler prepared by the method of the present invention is added to the material of the sock base material, and the socks woven have heat resistance, flame retardancy, aging resistance, wear resistance, and heat insulation properties. The prepared antibacterial and deodorizing socks are soft in texture, highly comfortable, safe and reliable, bright in color, and have broad-spectrum and long-lasting antibacterial and deodorizing effects.

[0022] The lanthanum and cerium raw materials in the rare earth composite functional filler prepared by the method of the present invention are high-abundance rare earth elements, the preparation process is simple, and the filler is green and environmentally friendly. The filler is suitable for promotion and application in the field of textiles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0024] Figure 1 This is a SEM image of the rare earth composite of Example 1 provided by the present invention;

[0025] Figure 2 This is an enlarged SEM image of the rare earth composite of Example 1 provided by the present invention;

[0026] Figure 3 This is a SEM image of the rare earth composite of Example 2 provided by the present invention;

[0027] Figure 4 This is a SEM image of the rare earth composite of Example 3 provided by the present invention;

[0028] Figure 5 This is a SEM image of the rare earth composite of Comparative Example 1 provided by the present invention;

[0029] Figure 6 This is a graph showing the E. coli test results of the rare earth composite functional filler of Example 1 provided by the present invention;

[0030] Figure 7 This is a graph showing the Staphylococcus aureus test results of the rare earth composite functional filler of Example 1 provided by the present invention;

[0031] Figure 8 This is a graph showing the Candida albicans test results of the rare earth composite functional filler of Example 1 provided by the present invention;

[0032] Fig. 9 This is a comparison chart of the antibacterial and deodorizing performance test data of the embodiment provided by the present invention and the comparative example 1. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0034] A method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks comprises the following steps:

[0035] S1. Preparation of rare earth and zinc carbonates: Add bottom water to the reactor, heat the bottom water temperature to 35°C under stirring, and then slowly add La with a concentration of 0.48 mol / L x Ce (1-x) Cl 3 solution and 2.28 mol / L ammonium bicarbonate solution, maintaining the pH of the reaction system at 6.5, La x Ce (1-x) Cl 3 After the solution was added, (La x Ce (1-x) ) 2 (CO 3 ) 3Precipitation, then continue to slowly add a 1.23 mol / L zinc chloride solution and a 2.28 mol / L ammonium bicarbonate solution at the same time, maintain the pH of the reaction system at 7, after the zinc chloride solution is added, the obtained precipitate is washed several times until the washing filtrate is detected by silver nitrate without precipitation, and filtered to obtain flaky rare earth and zinc carbonate;

[0036] S2. Preparation of rare earth composites: Add a certain amount of water and dispersant into a reactor, add rare earth and zinc carbonate under stirring to form a uniformly dispersed suspension, add the suspension into a silver nitrate solution containing a dispersant, stir and react for 4 hours, centrifuge and dehydrate, and calcine the obtained solid powder at a temperature of 500°C for 2 hours. Grind the calcined solid powder to a powder particle size of less than 1 μm to obtain a rare earth composite functional filler.

[0037] In some embodiments of the present application, La in step S1 x Ce (1-x) Cl 3 For La 0.1 Ce 0.9 Cl 3 ,La 0.36 Ce 0.64 Cl 3 and La 0.5 Ce 0.5 Cl 3 One of;

[0038] La x Ce (1-x) Cl 3 The solution is composed of La x Ce (1-x) Cl 3 , water and acetic acid, La x Ce (1-x) Cl 3 The mass ratio with acetic acid is 1:0.014.

[0039] In some embodiments of the present application, the mass concentration of rare earth and zinc carbonate in the suspension in step S2 is 10%, the amount of dispersant added is 1% of the mass of water, and the dispersant is polyvinyl pyrrolidone.

[0040] In some embodiments of the present application, the silver nitrate solution containing a dispersant in step S2 consists of silver nitrate, a dispersant and water, the mass concentration of silver nitrate in the solution is 10%, the amount of dispersant added is 0.1% of the mass of silver nitrate, and the dispersant is polyvinyl pyrrolidone.

[0041] In some embodiments of the present application, in step S2, the molar ratio of rare earth ions to zinc ions in the rare earth composite functional filler is 1:0.10-0.21, and the molar ratio of rare earth ions to silver is 1:0.01-0.03.

[0042] In some embodiments of the present application, the rare earth composite functional filler in step S2 is Ag, ZnO, La 2 O 2 CO 3 and CeO 2 The composition of the solid solution.

[0043] The present invention also provides the rare earth composite functional filler prepared by the above method as an antibacterial and deodorant agent, and the application of the rare earth composite functional filler in antibacterial and deodorant socks. 2% of the rare earth composite functional filler is added in the fiber production polymerization stage to prepare the antibacterial and deodorant fiber, and then 20% of the antibacterial and deodorant fiber is blended and interwoven with ordinary fibers to form socks, and finally the antibacterial and deodorant socks are made.

[0044] The core of the method of the present invention is:

[0045] 1) Rare earth composite functional filler is composed of Ag, ZnO, La 2 O 2 CO 3 and CeO 2 Composition, due to Ag 2 O is completely decomposed into Ag at a burning temperature of 400°C, and zinc carbonate is decomposed into ZnO and Ce at above 350°C. 2 (CO 3 ) 3 Decomposes into CeO at 400-500℃ 2 , La 2 (CO 3 ) 3 Decomposes into La at 500℃ 2 O 2 CO 3 The calcination temperature of 500℃ is beneficial to reduce the agglomeration of rare earth complexes, increase their specific surface area, enhance their antibacterial activity and the ability to adsorb and catalyze the decomposition of odorous compounds. If the calcination temperature is increased to above 900℃, La 2 (CO 3 ) 3 Decomposed into La 2 O 3 And enter CeO 2 In the crystal lattice, the rare earth complex slightly aggregates, the specific surface area decreases, and the antibacterial and deodorizing properties are significantly reduced.

[0046] 2) Since rare earth ions expose unfilled 4f electrons, they have strong coordination and complexing ability with bacteria and odor compounds to form stable compounds, inactivate bacteria, and improve their antibacterial and deodorizing abilities; at the same time, La 2 O 2 CO 3 and CeO 2 It also has the ability to adsorb and catalytically decompose odorous compounds and generate active oxygen, especially CeO 2 With Ce 3+ and Ce 4+ The reversible conversion characteristics of the oxidation state between CeO and CeO produce reactive oxygen species (ROS), which can kill and decompose bacteria. 2 As an antibacterial agent alone, the effect is not obvious. Since the amount of active oxygen produced by rare earth elements is low, the bactericidal effect is poor. 3+ 、Zn 2+ and Ag + Co-doped with CeO 2 By increasing oxygen vacancies in the medium, the antibacterial activity of reactive oxygen and the ability to adsorb and catalyze the decomposition of odorous compounds can be significantly enhanced through synergistic effects.

[0047] 3) The prepared rare earth composite functional filler is a flaky particle composed of primary grains less than 100nm. The flaky particles have a high specific surface area, resulting in a higher concentration of surface oxygen vacancies, thereby enhancing the generation of active oxygen; Ag is doped into ZnO-La 2 O 2 CO 3 -CeO 2 In the experiment, due to the large exposed area of ​​the crystal face, the flaky particle composite has higher bactericidal activity and the ability to adsorb and catalyze the decomposition of odorous compounds; in addition, Ag-CeO 2 With single CeO 2 Compared with the above, the antibacterial properties are significantly improved, because Ag weakens the Ce-O bond and enhances the production of ROS, thereby improving the antibacterial properties.

[0048] 4) Ag-ZnO-La 2 O 2 CO 3 -CeO 2 It can effectively control the release of Ag, avoiding the shortcomings of Ag having short-term antibacterial activity and rapid release of Ag. 2 O 2 CO 3 -CeO 2It can effectively control the oxidation and discoloration of elemental Ag by sulfur or other pollutants, and assist Ag to produce more active oxygen to participate in the antibacterial process. Silver and active oxygen can destroy the cell membrane structure of bacteria and inhibit the budding process of bacteria. Even Ag+ and nano-Ag particles can enter the bacterial cells to produce active oxygen, causing oxidative damage to bacterial nucleic acids, breakage of protein peptide chains, destruction of biofilms, etc., changing cell physiological activities and leading to bacterial death, thereby achieving a strong antibacterial effect. This shows that the rare earth complex has long-lasting antibacterial function and deodorizing performance.

[0049] 5) Ag-ZnO-La 2 O 2 CO 3 -CeO 2 Antibacterial composite materials added to fabrics significantly improve the antibacterial properties. 2+ It can interact synergistically with rare earth elements to enhance the activity of the generated electron-hole pairs, have a strong ability to destroy bacterial cells, and its antibacterial performance is significantly higher than that of single ZnO and La 2 O 2 CO 3 and CeO 2 The sum of effects.

[0050] 6) Highly effective antibacterial agents Ag and Zn 2+ Load in La 2 O 2 CO 3 -CeO 2 The carrier effectively enhances the stability and dispersibility of the antibacterial ions. The uniform loading on the carrier can exert the maximum antibacterial effect. The carrier has stable chemical properties and is not easily affected by high temperature and humid environment. 2 O 2 CO 3 -CeO 2 The carrier has good antibacterial activity and the ability to adsorb and catalyze the decomposition of odorous compounds. The flaky structure provides more active sites, which promotes La 3+ 、Ce 3+ 、Ag + and Zn 2+ The adsorption and contact rate of bacteria and odor compounds improves the antibacterial and anti-odor functions.

[0051] 7) The rare earth composite functional filler has good biocompatibility. The rare earth composite is added to the fiber during the spinning process and can be evenly dispersed in the textile socks. The antibacterial and deodorizing socks woven are durable and have long-lasting antibacterial and deodorizing functions.

[0052] Hereinafter, embodiments and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations are performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are weight references. Unless otherwise specified, the components used can all be purchased.

[0053] Embodiment 1:

[0054] See also Figure 1 and Figure 2 , a method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks, comprising the following steps:

[0055] Preparation of rare earth chloride solution: Add 2.4 mol of lanthanum chloride, 21.6 mol of cerium chloride, and 121.5 g of acetic acid into a stirring tank, dilute with water to a volume of 50 L, stir evenly, and obtain a rare earth chloride solution with a concentration of 0.48 mol / L.

[0056] Preparation of ammonium bicarbonate solution: Add 6.98 kg of ammonium bicarbonate to a stirring tank, dilute with water to a volume of 38.80 L, stir to dissolve, and obtain an ammonium bicarbonate solution with a concentration of 2.28 mol / L.

[0057] Preparation of zinc chloride solution: Add 5.04 mol of zinc chloride into a stirring tank, dilute with water to a volume of 4.10 L, stir evenly, and obtain a zinc chloride solution with a concentration of 1.23 mol / L.

[0058] Preparation of silver nitrate solution: Add 0.24 mol of silver nitrate and 0.041 g of polyvinyl pyrrolidone into a stirring tank, and dilute the silver nitrate solution to 10% with water.

[0059] 1) Preparation of rare earth and zinc carbonate: 5 L of bottom water was added to a 100 L reactor, and the bottom water was heated under stirring. The bottom water temperature was maintained at 35 ° C. The rare earth chloride solution and ammonium bicarbonate solution were added simultaneously at a flow rate ratio of 1:0.68, and the pH of the reaction system was maintained at 6.5. After the rare earth chloride solution was added, (La 0.1 Ce 0.9 ) 2 (CO 3 ) 3 Precipitation, then zinc chloride and ammonium bicarbonate are added simultaneously at a flow ratio of 1:1.11, the pH of the reaction system is maintained at 7, and after the zinc chloride solution is added, the obtained precipitate is filtered and washed several times until no precipitate is produced by silver nitrate detection of the washing filtrate, thereby obtaining rare earth and zinc carbonates;

[0060] 2) Preparation of rare earth composite: rare earth and zinc carbonate, water and dispersant are added into a reaction kettle, the concentration of rare earth and zinc carbonate is adjusted to 10% with water, the amount of dispersant polyvinyl pyrrolidone added is 1% of the amount of water, and stirred evenly to form a uniformly dispersed suspension, the suspension is added into the above silver nitrate solution, stirred for reaction for 4 hours, centrifuged for dehydration, the obtained solid powder is calcined at 500°C for 2h, and ground until the powder particle size is less than 1μm to obtain a rare earth composite functional filler.

[0061] Figure 1 The SEM image of the rare earth composite of this example shows that the surface of the rare earth composite is composed of fine particles connected into flaky particles, the thickness of the flaky particles is 100 nm, and the flaky particles are monodisperse.

[0062] Figure 2 This is an enlarged SEM image of the rare earth composite of this example. As can be seen from the image, the surface of the obtained rare earth composite is linked by particles smaller than 100 nm, and there are many gaps and holes between the particles.

[0063] The present invention provides a rare earth composite functional filler prepared by the method, and application of the rare earth composite functional filler in antibacterial and deodorizing socks.

[0064] 2% of rare earth composite functional filler is added in the fiber production polymerization stage to obtain antibacterial and deodorant fiber, and then 20% of the antibacterial and deodorant fiber is blended and interwoven with ordinary fiber to form socks, and finally the antibacterial and deodorant socks are made.

[0065] Embodiment 2:

[0066] See also Figure 3 , a method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks, comprising the following steps:

[0067] Preparation of rare earth chloride solution: Add 8.64 mol of lanthanum chloride, 15.64 mol of cerium chloride, and 121.5 g of acetic acid into a stirring tank, dilute with water to a volume of 50 L, stir evenly, and obtain a rare earth chloride solution with a concentration of 0.48 mol / L.

[0068] Preparation of ammonium bicarbonate solution: Add 6.66 kg of ammonium bicarbonate into a stirring tank, dilute with water to a volume of 37.01 L, stir to dissolve, and obtain an ammonium bicarbonate solution with a concentration of 2.28 mol / L.

[0069] Preparation of zinc chloride solution: Add 3.6 mol of zinc chloride to a stirring tank, dilute with water to a volume of 2.93 L, stir evenly, and obtain a zinc chloride solution with a concentration of 1.23 mol / L.

[0070] Preparation of silver nitrate solution: Add 0.48 mol of silver nitrate and 0.082 g of polyvinyl pyrrolidone into a stirring tank, and dilute the silver nitrate solution to 10% with water.

[0071] 1) Preparation of rare earth and zinc carbonate: 0.36 Ce 0.64 ) 2 (CO 3 ) 3 The precipitation replaces the (La 0.1 Ce 0.9 ) 2 (CO 3 ) 3 Precipitation, the rest is the same as 1) in Example 1.

[0072] 2) Preparation of rare earth composite: same as 2) in Example 1. Figure 3 The SEM image of the rare earth composite of this example shows that the surface of the rare earth composite is composed of fine particles connected into flaky particles, the thickness of the flaky particles is 100 nm, and the flaky particles are monodisperse.

[0073] The present invention provides a rare earth composite functional filler prepared by the method, and application of the rare earth composite functional filler in antibacterial and deodorizing socks.

[0074] 2% of rare earth composite functional filler is added in the fiber production polymerization stage to obtain antibacterial and deodorant fiber, and then 20% of the antibacterial and deodorant fiber is blended and interwoven with ordinary fiber to form socks, and finally the antibacterial and deodorant socks are made.

[0075] Embodiment 3:

[0076] See also Figure 4 , a method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks, comprising the following steps:

[0077] Preparation of rare earth chloride solution: Add 12 mol of lanthanum chloride, 12 mol of cerium chloride, and 120.6 g of acetic acid into a stirring tank, dilute with water to a volume of 50 L, stir evenly, and obtain a rare earth chloride solution with a concentration of 0.48 mol / L.

[0078] Preparation of ammonium bicarbonate solution: Add 6.42 kg of ammonium bicarbonate to a stirring tank, dilute with water to a volume of 35.67 L, stir to dissolve, and obtain an ammonium bicarbonate solution with a concentration of 2.28 mol / L.

[0079] Preparation of zinc chloride solution: Add 2.4 mol of zinc chloride to a stirring tank, dilute with water to a volume of 1.95 L, stir evenly to obtain a zinc chloride solution with a concentration of 1.23 mol / L.

[0080] Preparation of silver nitrate solution: Add 0.72 mol of silver nitrate and 0.122 g of polyvinyl pyrrolidone into a stirring tank, and dilute the silver nitrate solution to 10% with water.

[0081] 1) Preparation of rare earth and zinc carbonate: 0.5 Ce 0.5 ) 2 (CO 3 ) 3 The precipitation replaces the (La 0.1 Ce 0.9 ) 2 (CO 3 ) 3 Precipitation, the rest is the same as 1) in Example 1.

[0082] 2) Preparation of rare earth composite: same as 2) in Example 1. Figure 4 The SEM image of the rare earth composite of this example shows that the surface of the obtained rare earth composite is composed of fine particles connected into flaky particles, the thickness of the flaky particles is 150nm, and the flaky particles are monodisperse.

[0083] The invention provides a rare earth composite functional filler prepared by the method, and application of the rare earth composite functional filler in antibacterial and deodorizing socks.

[0084] 2% of rare earth composite functional filler is added in the fiber production polymerization stage to obtain antibacterial and deodorant fiber, and then 20% of the antibacterial and deodorant fiber is blended and interwoven with ordinary fiber to form socks, and finally the antibacterial and deodorant socks are made.

[0085] Comparative Example 1:

[0086] See also Figure 5 and Fig. 9 The preparation of rare earth chloride solution, ammonium bicarbonate solution, zinc chloride solution and silver nitrate solution are the same as those in Example 1.

[0087] 1) Preparation of rare earth and zinc carbonates: same as 1) in Example 1;

[0088] 2) Preparation of rare earth composite: The solid powder is calcined at 900° C. instead of calcined at 500° C. in Example 1, and the rest is the same as 2) in Example 1. Figure 5 The SEM image of the rare earth composite of this comparative example shows that the surface of the obtained rare earth composite has a sintering phenomenon, which reduces the surface activity of the rare earth composite.

[0089] The invention provides a rare earth composite functional filler prepared by the method, and application of the rare earth composite functional filler in antibacterial and deodorizing socks.

[0090] 2% of rare earth composite functional filler is added in the fiber production polymerization stage to obtain antibacterial and deodorant fiber, and then 20% of the antibacterial and deodorant fiber is blended and interwoven with ordinary fiber to form socks, and finally the antibacterial and deodorant socks are made.

[0091] According to the national standard "GB / T20944.3-2008", the antibacterial and deodorant socks prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were respectively tested for their antibacterial properties, and the antibacterial and deodorant socks were washed 150 times. According to the national standard "GB / T33610.2-2017", the antibacterial and deodorant socks prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were respectively tested for their deodorant properties. The test results are shown in Tables 1 and Fig. 9 As shown, Fig. 9 This is a comparison chart of the antibacterial and deodorizing performance test data of the antibacterial and deodorizing socks prepared in Example 1, Example 2, Example 3 and Comparative Example 1;

[0092]

[0093]

[0094] Table 1

[0095] According to Table 1 and Fig. 9 From the test results shown, it can be seen that the antibacterial performance and the ability to adsorb and catalyze the decomposition of odorous compounds of the antibacterial and deodorizing socks woven in Comparative Example 1 are significantly reduced compared with those in Example 1, which proves the antibacterial effect and reliability of the rare earth composite functional filler of the present invention in the antibacterial and deodorizing socks.

[0096] The antibacterial performance test experiment was carried out on the rare earth composite functional filler prepared in Example 1:

[0097] Test Materials:

[0098] Main instruments and equipment: high-temperature and high-pressure steam autoclave (Hirayama HVE-50), clean workbench (Sujing Antai SW-CJ-2FD), constant temperature oscillator (USA Crystal IS-RDV1), analytical electronic balance (Changzhou Lucky FA2004), electric constant temperature incubator (Shanghai Zhicheng ZXDP-B2160);

[0099] Main reagents: LB broth medium (Shengang, catalog number: A507002), agar powder (Shengang, catalog number: A505255-0250), potato dextrose agar medium (Solabo, catalog number: P8931), potato dextrose broth (Solabo, catalog number: P9240);

[0100] Strains: Staphylococcus aureus (No.: ATCC29213), Escherichia coli (No.: ATCC25922), Candida albicans (No.: ATCC10231);

[0101] Experimental steps:

[0102] 1. Culture medium preparation: LB liquid culture medium - use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 121°C for 15 minutes and set aside for use.

[0103] LB solid culture medium - use a measuring cylinder to measure 100mL of distilled water and pour it into a 250mL reagent bottle. Use an analytical electronic balance to weigh 2.5g of LB broth culture medium and 1.5g of agar powder respectively. Add the above weighed reagents and mix well. Sterilize in a high-temperature and high-pressure steam sterilizer at 121℃ for 15min. When the culture medium cools to about 40-50℃, use an electric pipette to draw 15mL of culture medium and pour it into a disposable sterile plate.

[0104] PDB liquid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 3.5 g of potato dextrose broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam autoclave at 121°C for 20 minutes. After cooling to room temperature, place it in a 4°C refrigerator for later use.

[0105] PDA solid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 4.6 g of potato dextrose agar culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 115°C for 20 minutes. When the culture medium cools to about 40-50°C, use an electric pipette to draw 20 mL of the culture medium and pour it into a disposable sterile plate.

[0106] 2. Preparation of bacterial suspension: Take three 12mL bacterial culture tubes, add 3mL LB liquid medium to each, pick single colonies from the solid culture medium of Staphylococcus aureus and Escherichia coli and add them to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature oscillator (37℃, 200rpm) and shake culture overnight (15h).

[0107] Take two 12mL bacterial culture tubes, add 3mL PDB liquid culture medium to each, pick a single colony from the Candida albicans solid culture medium and add it to the liquid culture medium, and use the other tube as a blank control. Place it in a constant temperature oscillator (28℃, 200rpm) for 24h of shaking culture.

[0108] 3. Sample processing: Weigh 0.5g of rare earth material sample, put it into a disposable culture dish according to the group, soak it in 75% ethanol for 60 minutes, dry it and set it aside.

[0109] 4. Experimental groups: blank, rare earth material (rare earth composite functional filler prepared by the method of Example 1).

[0110] 5. Co-culture + plate spreading count test: Use sterile PBS solution to dilute the bacterial solutions of Candida albicans, Staphylococcus aureus and Escherichia coli to 10 4 CFU / mL. Transfer the samples to 250mL conical flasks, add 100mL of diluted bacterial solution to each flask, and add no sample to the blank control group. Place in a 37℃ / 28℃ constant temperature incubator and shake for 24h.

[0111] After the culture is completed, the bacterial solution is diluted 10 times with sterile PBS solution, and 100 μL of the dilution is evenly spread on the LB / PDA solid medium. Place it in a 37℃ / 28℃ constant temperature incubator for 18h / 48h, take it out, take pictures and record the number of colonies.

[0112] 6. Experimental results:

[0113] See also Figures 6 to 8 , the colony count is the colony count result under the corresponding dilution multiple of each group. The counting principle is based on the national standard GB4789.2-2022. The colony count is selected between 30CFU and 300CFU for colony counting. At the minimum dilution multiple, if there is still no colony growth, it proves that the sample has obvious antibacterial effect;

[0114] The calculation method of bacterial solution concentration (CFU / mL) is: colony count × dilution factor × 10 (0.1 mL coating);

[0115] Antibacterial rate = (1-concentration of bacterial solution in experimental group / concentration of bacterial solution in control group) × 100%.

[0116] E. coli test results Figure 6 As shown in Table 2:

[0117]

[0118]

[0119] Table 2

[0120] Staphylococcus aureus test results Figure 7 As shown in Table 3:

[0121]

[0122] Table 3

[0123] Candida albicans test results Figure 8 As shown in Table 4:

[0124]

[0125] Table 4

[0126] This experiment conducted a comprehensive antibacterial performance test on the rare earth composite functional filler prepared in Example 1. The experimental results showed that compared with the blank control group, the experimental group using the rare earth composite functional filler showed a very significant antibacterial effect in the antibacterial test of Escherichia coli. The colony count of the blank control group was 158, while the experimental group had no colony growth at all, indicating that the antibacterial rate of rare earth materials on Escherichia coli reached more than 99.94%. This result fully proves that the rare earth composite functional filler has a strong inhibitory effect on Escherichia coli. In the antibacterial test of Staphylococcus aureus, the rare earth composite functional filler also showed excellent antibacterial performance. The colony count of the blank control group was 43, while the experimental group also had no colony growth, and the antibacterial rate exceeded 99.98%. This data further verified the high-efficiency antibacterial ability of rare earth materials on Staphylococcus aureus. For the antibacterial test of Candida albicans, the antibacterial rate was as high as more than 98.31%. This shows that the rare earth composite functional filler also has a strong inhibitory effect on Candida albicans.

[0127] In summary, the rare earth composite functional filler prepared by the method of the present application has shown significant antibacterial effects in the antibacterial performance tests against Escherichia coli, Staphylococcus aureus and Candida albicans. The filler not only has a broad antibacterial spectrum, but also has strong antibacterial performance. The application of rare earth composite functional fillers in antibacterial and deodorizing socks has significant antibacterial performance and deodorizing effects.

[0128] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks, characterized in that: The steps include: S1. Preparation of rare earth and zinc carbonates: Add bottom water to the reactor, heat the bottom water temperature to 35°C under stirring, and then slowly add La with a concentration of 0.48 mol / L x Ce (1-x) Cl3 solution and 2.28 mol / L ammonium bicarbonate solution, maintaining the pH of the reaction system at 6.5, La x Ce (1-x) After the addition of Cl3 solution, (La x Ce (1-x) )2(CO3)3 precipitate, then continue to slowly add a 1.23 mol / L zinc chloride solution and a 2.28 mol / L ammonium bicarbonate solution at the same time, maintain the pH of the reaction system at 7, after the zinc chloride solution is added, the obtained precipitate is washed several times until the washing filtrate is detected with silver nitrate and no precipitate is produced, and filtered to obtain flaky rare earth and zinc carbonate; S2. Preparation of rare earth composites: Add a certain amount of water and dispersant into a reactor, add rare earth and zinc carbonate under stirring to form a uniformly dispersed suspension, add the suspension into a silver nitrate solution containing a dispersant, stir and react for 4 hours, centrifuge and dehydrate, and calcine the obtained solid powder at a temperature of 500°C for 2 hours. Grind the calcined solid powder to a powder particle size of less than 1 μm to obtain a rare earth composite functional filler.

2. The method for preparing a rare earth composite functional filler for antibacterial and deodorizing socks according to claim 1, characterized in that: In step S1, La x Ce (1-x) Cl3 is La 0.1 Ce 0.9 Cl3、La 0.36 Ce 0.64 Cl3 and La 0.5 Ce 0.5 One of Cl3; La x Ce (1-x) Cl3 solution is composed of La x Ce (1-x) Cl3, water and acetic acid, La x Ce (1-x) The mass ratio of Cl3 to acetic acid is 1:0.

014.

3. The method for preparing the rare earth composite functional filler for antibacterial and deodorizing socks according to claim 1, characterized in that: In step S2, the mass concentration of rare earth and zinc carbonate in the suspension is 10%, the amount of dispersant added is 1% of the mass of water, and the dispersant is polyvinyl pyrrolidone.

4. The method for preparing the rare earth composite functional filler for antibacterial and deodorizing socks according to claim 1, characterized in that: The silver nitrate solution containing a dispersant in step S2 is composed of silver nitrate, a dispersant and water. The mass concentration of silver nitrate in the solution is 10%, the amount of the dispersant added is 0.1% of the mass of the silver nitrate, and the dispersant is polyvinyl pyrrolidone.

5. The method for preparing the rare earth composite functional filler for antibacterial and deodorizing socks according to claim 1, characterized in that: In step S2, the molar ratio of rare earth ions to zinc ions in the rare earth composite functional filler is 1:0.10-0.21, and the molar ratio of rare earth ions to silver is 1:0.01-0.

03.

6. The method for preparing the rare earth composite functional filler for antibacterial and deodorizing socks according to claim 1, characterized in that: In step S2, the rare earth composite functional filler is a solid solution composed of Ag, ZnO, La2O2CO3 and CeO2.

7. Use of the rare earth composite functional filler prepared by the method according to any one of claims 1 to 6 as an antibacterial and deodorizing agent, and use of the rare earth composite functional filler in antibacterial and deodorizing socks.

Citation Information

Patent Citations

  • Inorganic complex antimicrobials containing zincium-rare earth as well as preparation method and application thereof

    CN101176468B

  • Polymer-based cerium-doped nano-zinc oxide composite antibacterial agent for fabrics and its preparation method

    CN105648745B

  • A kind of preparation method of pearl antibacterial and deodorant socks

    CN105901782B

  • A kind of preparation technology of nano silver wire antibacterial and deodorant socks

    CN106473240B

  • Inorganic antiseptic of RE activated silver carrying matter and its prepn

    CN1313005C